Twisted forms of finite étale extensions and separable polynomials - Frank DeMeyer (International Journal of Mathematics and Mathematical Sciences)
Examples of twisted forms of finite étale extensions and separable polynomials are calculated using Mayer-Vietoris sequences for non-abelian cohomology.